(untitled) (Research, Society and Development, 2022)
Objective: to investigate, among medicine professors, the perception of the Self-Efficacy (AE) belief in teaching and its associated factors. Method: study with a quantitative approach, observational, analytical, carried out with 60 professors of the medical course of a federal educational institution. For data collection, the Woolfolk and Hoy (2001) teacher self-efficacy scale, validated in Brazil by Bzuneck and Guimarães (2003), and the Maslach Burnout Inventary were used. The chi-square test was applied to verify if there was a significant difference between participants who had moderate and high burnout and low self-efficacy. The variables were tested using logistic regression to identify possible risk factors for low self-efficacy. Univariate analysis was used and variables with p < 0.20 were selected for multivariate analysis. For the chi-square test, a confidence level of 95% was used. Results: of the 60 professionals studied, 11 (18.3%) had low AE and 49 (81.7%) had high AE. AE had a mean of 3.2±0.8 points, with a median of 3.3 and 95% CI. High Burnout was observed as an associated factor in 25.7% (of the participants identified with low self-efficacy, which may indicate that AE is one of the variables that interfere in the development of the syndrome. Regarding the sociodemographic variables, 31 (51.7%) teachers participating in the study were female, the predominant age group was 50 years or older (63.4%), the majority (91.7%) had a steady partner and two children (53.3%) Regarding teaching time, most 36 (60.0%) reported having more than 15 years of experience; 38 (63.3%) taught at undergraduate and graduate levels at the same time; 55 (91.7%) stated that teaching was not their main activity and 43 (71.6%) worked as professionals. Conclusion: The perception of self-efficacy in teaching is positive (high) in the studied group, with Burnout syndrome being the main factor associated with low self-efficacy. The most relevant risk factors for low self-efficacy were being female, ≥ 50 years old, not being in a steady relationship, not having children and not being exclusively dedicated to teaching, working time ≥15 years, absence of an effective bond as a public servant. The results of this study can be used to improve institutional management and teaching practice.